Diagnosis of genitourinary tuberculosis: detection of mycobacterial lipoarabinomannan and MPT-64 biomarkers within urine extracellular vesicles by nano-based immuno-PCR assay - Ekta Kamra; Tulika Prasad; Anam Rais; Bhawna Dahiya; Abhishek Sheoran; Aishwarya Soni; Suman Sharma; Promod K. Mehta (Scientific Reports, 2023)
Abstract We detected a cocktail of Mycobacterium tuberculosis lipoarabinomannan (LAM) and MPT-64 biomarkers within urine extracellular vesicles (EVs) of genitourinary TB (GUTB) patients by nano-based immuno-PCR (I-PCR) assay, i.e., magnetic bead-coupled gold nanoparticle-based I-PCR (MB-AuNP-I-PCR) and compared the results with I-PCR and Magneto-ELISA. The size (s) of urine EVs ranged between 52.6 and 220.4 nm as analyzed by transmission electron microscopy (TEM) and nanoparticle tracking analysis. Functionalized AuNPs (coupled with detection antibodies/oligonucleotides) were characterized by UV–vis spectroscopy, TEM, ELISA, PCR, Atomic Force Microscopy and Fourier Transform Infrared spectroscopy, while conjugation of capture antibodies with MBs was validated by UV–vis spectroscopy and Magneto-ELISA. Our MB-AuNP-I-PCR exhibited sensitivities of 85% and 87.2% in clinically suspected (n = 40) and total (n = 47) GUTB cases, respectively, with 97.1% specificity in non-TB controls (n = 35). These results were further authenticated by the quantitative SYBR Green MB-AuNP-real-time I-PCR (MB-AuNP-RT-I-PCR). Concurrently, I-PCR and Magneto-ELISA showed sensitivities of 68.1% and 61.7%, respectively in total GUTB cases, which were significantly lower (p < 0.05–0.01) than MB-AuNP-I-PCR. Markedly, a wide range (400 fg/mL–11 ng/mL) of LAM+MPT-64 was quantified within urine EVs of GUTB cases by SYBR Green MB-AuNP-RT-I-PCR, which can assess the disease dynamics. This study will certainly improve the current algorithms used in GUTB diagnostics.